Registration of Rights Transfer of Land Due to Instruction Related to Development of Collective Rights Sharing (APHB) - Arrofi'atush Sholihah; Ahmad Khisni (Sultan Agung Notary Law Review, 2021)
The results of research and discussion suggest that the transfer of rights due to inheritance occurs at the time of a person's death. In a sense, that since then the heirs became the new rights holders. As to who is the heir is stipulated in the applicable civil law. If the heirs are more than one person, and the heirs agree to appoint one of the heirs as the rights holder who will be listed in the certificate by making an inheritance certificate and an affidavit of the heirs, then by PPAT will be made APHB as the basis for the transfer of rights with the approval of all heirs. The purpose of this research is to know the process of implementing the registration of transfer of rights due to inheritance related to APHB, Legal consequences for the registration of land rights transfer due to inheritance related to APHB and the creation of APHB Deed. This study uses empirical juridical approach method with data collection techniques through primary data and secondary data. To collect primary data is done with field research using interviews. While the secondary data is obtained by reviewing primary legal materials and secondary legal materials, which are then analyzed using qualitative analysis techniques and interpreted logically and systematically which are then concluded.